Fugler i Norge 2004 – Rapport fra Norsk faunakomite for fugl (NFKF) - Reinsborg, Tore; Berge, Torborg; Dahl, Espen Lie; Kamsvåg, Christer; Størkersen, Øystein R. (Ornis Norvegica, 2008)
THE NORWEGIAN BIRD REPORT 2004 - a report on locally uncommon and scarce birds in Norway in 2004, by the Norwegian Birds Records Committee (NFKF) The basis of this report is the annual reports produced by the county rarities committees. For 2004 all the counties contributed to the report, although Finnmark, Troms, Sogn & Fjordane, Rogaland and Vest-Agder counties did not publish own county reports. We believe this report reflects fairly well observations from Norway in 2004. Readers should take care to note the geographical or time delimitation of the records stated for the different species, as stated in codes immediately after the scientific name of the species. The Norwegian Birds Records Committee (NFKF) has been publishing annual reports since 1991. The occurrence of Bewick’s Swan Cygnus columbianus was one of the poorest in NFKFs history, and the occurence of Lesser White-fronted Geese Anser erythropus at the traditional feeding and roosting site Valdakmyra, Porsanger (FI) continued to be very low. White-fronted Geese Anser albifrons was seen in good numbers. Mandarin Ducks Aix galericulata occurred in record high numbers. Gadwalls Anas strepera have occurred in steadily increasing numbers in Norway in recent years, and 2004 was the second best year to date for this species. Quails Coturnix coturnix occurred in good numbers for the third year in succession. Yellowbilled Divers Gavia adamsii experienced the second best year since 1991. Leach’s Storm Petrel Oceanodroma leucorhoa was seen in record high numbers in Rogaland in September. Many Common Kestrels Falco tinnunculus were seen during the winter months. The Eurasian Hobby Falco subbuteo is a raptor that has occurred in high numbers in recent years, and 2004 was the second best year ever. The occurrence of Avocets Recurvirostra avosetta was the best ever in NFKFs history. Several shorebirds, such as European Golden Plovers Pluvialis apricaria, Northern Lapwings Vanellus vanellus, Great Knots Calidris canutus, Sanderlings Calidris alba and Woodcocks Scolopax rusticola wintered in low numbers. The number of migrating Broad-billed Sandpipers Limicola falcinellus was the second best in NFKFs history. Migrating Pomarine Skuas Stercorarius pomarinus and Long-tailed Skuas Stercorarius longicaudus were seen in good numbers, and the occurrence of Little Gulls Larus minutus was the second best in NFKFs history. Compared to the last three years, Glaucous Gulls Larus hyperboreus occurred in considerable lower numbers in 2004. Also the occurrence of Snowy Owls Bubo scandiaca and Great Grey Owls Strix nebulosa were very poor. The negative trend related to migrating Horned Larks Eremophila alpestris continued in 2004, and the last five years represent the five poorest years for this species. The occurrence of Red-throated Pipits Anthus cervinus was one of the poorest in NFKFs history, while Yellow Wagtails Motacilla flava flavissima and Pied Wagtails Motacilla alba yarrellii occurred in near record numbers. Many breeding attempts of Waxwings Bombycilla garrulus were recorded, especially in Nordland county. Stonechats Saxicola torquata occurred in record high numbers, and nine confirmed breeding pairs were recorded. The number of singing Common Grasshopper Warblers Locustella naevia was the highest ever recorded, and the number of Marsh Warblers Acrocephalus palustris and Redbreasted Flycatchers Ficedula parva continued to be high. Many breeding attempts of Red-backed Shrikes Lanius collurio were recorded in Rogaland county, and Great Grey Shrikes Lanius excubitor had another good year throughout the country. The Eurasian Tree Sparrow Passer montanus still show a marked increase in the north of its distribution range, especially in Nord- Trøndelag county. In November, the southernmost parts of Norway experienced a major influx of Pine Grosbeaks Pinicola enucleator producing record numbers in the history of NFKF. In October, Norway also had a major influx of Bullfinches Pyrrhula pyrrhula. These Bullfinches probably came from other parts of Europe than Fennoscandia. The Ortolan Bunting Emberiza hortulana continued to occur in low numbers and the Rustic Bunting Emberiza rustica experienced the poorest year in NFKFs history. The occurrence of Little Buntings Emberiza pusilla was very good.